Effect of thermal and non-thermal processing on fermentable oligo-di-monosaccharides and polyols (FODMAPs) content in millet, sorghum, soybean and sesame varieties - Docus Alowo; Docus Alowo; Solomon Olum; Ivan Muzira Mukisa; Duncan Ongeng (Frontiers in Nutrition, 2025)
This study investigated the effect of processing (roasting and malting) and crop variety on fermentable oligo-di-monosaccharides and polyols (FODMAPs) profile of millet, sorghum, soybean, and sesame varieties commonly consumed in Uganda. Two elite varieties and one indigenous variety for each crop were analyzed. Monosaccharide and polyols content was determined by HPLC-UV method, while disaccharides and oligosaccharide were determined using Megazyme kits. The elite varieties of soybean (Maksoy 3 N), Millet (Seremi 2) and sorghum (Narosorg 2) exhibited significantly (p < 0.05) lower oligosaccharide content compared to indigenous varieties with percentage differences ranging from 10.2 to 73.9%. Additionally, Maksoy 3 N and Narosorg 2 also exhibited significantly lower (p < 0.05) excess fructose content compared to the indigenous variety. Malting was more effective than roasting (p < 0.05) in reducing FODMAP categories and total FODMAP content. Malting effectively reduced excess fructose in all grain types to the recommended levels of <0.15 g/100 g compared to roasting. Moreover, malting reduced total oligosaccharides and total FODMAPs in soybean and sesame by more than 50%. However, this reduction did not achieve the recommended threshold of 0.3 g/100 g for total oligosaccharides and 0.5 g/100 g, for total FODMAPs which are a criterion to categorize low FODMAP diets. Malting conditions should be optimized to enhance its effectiveness in producing low FODMAP foods. This study highlights the importance of selecting appropriate grain variety and processing techniques that modify FODMAP content in foods that can be used for dietary therapy of gastro-intestinal disorders among vulnerable population.